Tinjauan Teoritis tentang Etika Periklanan dalam Praktik Endorsement Berbayar bagi Generasi Z di Era Digital - Aysah Aurellia Rosspertiwi; Sabrina Zulfanova Saputri; Nida Aisyah; Daniel Handoko (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study examines ethical issues in paid endorsement practices on social media targeting Generation Z in the digital era. Using a literature review approach, the article compiles and analyzes 15 relevant national and international sources to identify the ethical values expected by Gen Z in consuming digital advertisements. The findings show that transparency, authenticity, and credibility are the main principles that influencers and brands must uphold for their marketing communication to be positively received by younger audiences. Moreover, there is an urgent need to establish stronger regulations and enhance media literacy education to empower Gen Z in critically evaluating covert commercial content. These findings hold significant implications for policymakers, communication industry practitioners, and scholars in shaping ethical and sustainable digital advertising practices.